Integrating Folklore into Language and Literature Learning to Strengthen Character Education - Alfian Rokhmansyah; Widyatmike Gede Mulawarman; Yusak Hudiyono; Nina Queena Hadi Putri; Muhammad Ma'rifan Nur (DISASTRA: PENDIDIKAN BAHASA DAN SASTRA INDONESIA, 2026)
This study investigates how East Kalimantan folktales can be integrated into Indonesian language and literature learning to strengthen character education. This study aims to achieve two objectives: (1) to identify and analyze character values embedded in East Kalimantan folktales, and (2) to examine how these values can be translated into learning activities. This study employs a qualitative narrative-ethnographic design, focusing on folklore in three regencies (West Kutai, East Kutai, and Kutai Kartanegara) in East Kalimantan. The data were analyzed through content analysis and interactive model, supported by source and method triangulation. The findings show that the folktales consistently articulate character values related to the self (responsibility, perseverance, sincerity, gratitude, humility), to others (social concern, cooperation, justice, empathy, respect for human dignity), and to divinity (religiosity and devotion), which are narratively modeled through characters’ actions, decisions, and dialogue. These values can be systematically integrated into learning objectives, materials, activities, and assessment through folklore-based reading, discussion, dramatization, reflective writing, value clarification, and rubric- and portfolio-based evaluation. The study concludes that East Kalimantan folklore constitutes pedagogically robust core content for contextual, narrative-based character education in language and literature classrooms.